Rheological properties of regular insulin and aspart insulin Langmuir monolayers at the air/water interface: Condensing effect of Zn2+ in the subphase - Grasso, Ernesto Javier (2014)
The interfacial behavior of regular insulin (Reg-insulin) and aspart insulin (Asp-insulin) was critically affected by the presence of Zn2+ in the subphase. This cation induced a condensed-like behavior in the compression isotherms, especially apparent for Reg-insulin films when observed by Brewster angle microscopy. Immediately after spreading, Reg-insulin, but not Asp-insulin, showed bright patches that moved in a gaseous-like state. Moreover, Zn2+ caused marked variations of the surface electrostatics of both insulin monolayers and considerable hysteresis of their molecular organization. By oscillatory compression–expansion cycles, we observed in all cases the development of a dilatational response to the surface perturbation, and both monolayers exhibited well-defined shear moduli in the presence of Zn2+, which was higher for Reg-insulin. Development of a shear modulus indicates behavior resembling a nominal solid, more apparent for Reg-insulin than for Asp-insulin, suggesting the presence of viscoelastic networks at the surface.